Estresse em fisioterapeutas que atuam na reabilitação ortopédica nas cidades de Goiânia e Aparecida de Goiânia - Maia, Mauricio Silveira (2014)
Introduction: Stress first described in 1936 by Hans Selye, it occurs due to stimuli that trigger the aggression physiological changes in the body. The answers can be positive (eustress) or negative (distress), this subdivided into three stages of alarm, resistance and exhaustion. Physiotherapists working in orthopedic rehabilitation coexist with stressors that can lead to job stress. Objectives: Develop an integrative review on stress in health professionals, with an emphasis on physical therapists. Define the socio demographic profile and professional characteristics of physiotherapists working in orthopedic rehabilitation in the cities of Goiânia and Aparecida de Goiânia. Determine the incidence and the association between stress and factors in the work activity of these physiotherapists. Methodology: This study was divided into two studies. The first integrative review on stress in the work activities of the physiotherapist. Initially descriptors were defined both in MeSH, as in MeSH, after used for data collection through databases SciELO, LILACS, Cochrane and PubMed, for the period August 2013 to July 2014. 8357 articles were found 17 were included in the study after primary selection by date of publication (1994-2014) and the language used (English, Portuguese and Spanish). The secondary selection occurred by reading the titles and abstracts later. Selected articles were tabulated according to the methodological format (literature review, qualitative and quantitative studies). The second study consisted of a quantitative survey, observational, cross-sectional, of which 72 physiotherapists participated, 34 females and 39 males, between 22 and 42 years who work in orthopedic rehabilitation in the cities of Goiânia and Aparecida de Goiânia. All participants completed a demographic questionnaire and professional characteristics developed by the authors and the Inventory of Stress Symptoms for Adults Lipp (ISSL). The results were quantified and tabulated in frequency and percentage using Microsoft Office Excel 2007. The software relationship between the presence of stress and sociodemographic variables were evaluated by chi-square test with the Statistical Package for the Social Sciences, version 20 (SPSS, Chicago, IL). Abstract xvii Results: The first study found 17 articles, four of literature review, two qualitative and 11 quantitative methodology. The selected articles, 12 were published in English, one in Spanish and four articles in Portuguese. Few studies are found about the presence of stress on physical therapists, however it is present in some workplaces. The factors generating stress were: inadequate work, insufficient human resources, relations between unsatisfactory professional, high-volume activities, limited time, excessive bureaucracy, conflicts of function and autocratic management environment. The second study shows that the proportion of men and women physiotherapists found in this study was similar. The Profile of professionals working with the orthopedic rehabilitation in the city of Goiânia and Aparecida de Goiânia is on average 22.7 years old with 4.5 years of graduation on average, predominantly working in clinics (38.9%), where 69.4% of all physical therapists have not evaluated CLT contract. The smaller number of patients seen per week was 3 and the highest 200, with an average of 56.3 patients per week, 43.1% worked 30 hours per week, 80.6% practice physical exercises and 73.6% earn above 2,490 actual monthly. Most have other labor activity (75%) and 43.6% have specialist titration. About having children, a large number of explicitly 84.7% do not have children, and 66.7% are single. 62.5% believe that work interferes with personal life and 86.1% did not think of changing professions. Physiotherapists evaluated, 33 (46%) had stress, 2 (6%) was in the alert phase, 26 (79%) in the resistance stage and five physiotherapists were at the stage of exhaustion. The workplace was the only variable that was significant (p = 0.024) in association with stress. Among workplaces, clinics were the most favorable sites for the emergence of stress on physical therapists, physiotherapists where 28 were evaluated and 17 of them (24%) had stress. The association between clinical practice and also generated a lot of stress on physical therapists evaluated. Conclusion: The stress is present in the majority of health professionals, including physiotherapists due to the characteristics of the profession. The vast majority of physiotherapists evaluated are young, single, have no children and do physical activities. Usually work in clinics, a fact that influenced the emergence of stress. Serve many patients and have no contract CLT. Usually work at least 30 hours per week, earning mostly above Abstract xviii 2,490 reais a month and usually has more than one job. Most have minimal titration expert and not think about changing professions. It is necessary to conduct further studies with larger numbers of physiotherapists to verify the role of other stressors, because stress can influence the quality of life of the professional and the service provided to the patient.